2020
DOI: 10.3174/ajnr.a6499
|View full text |Cite
|
Sign up to set email alerts
|

Advanced ADC Histogram, Perfusion, and Permeability Metrics Show an Association with Survival and Pseudoprogression in Newly Diagnosed Diffuse Intrinsic Pontine Glioma: A Report from the Pediatric Brain Tumor Consortium

Abstract: BACKGROUND AND PURPOSE: Diffuse intrinsic pontine glioma is a lethal childhood brain cancer with dismal prognosis and MR imaging is the primary methodology used for diagnosis and monitoring. Our aim was to determine whether advanced diffusion, perfusion, and permeability MR imaging metrics predict survival and pseudoprogression in children with newly diagnosed diffuse intrinsic pontine glioma. MATERIALS AND METHODS: A clinical trial using the poly (adenosine diphosphate ribose) polymerase (PARP) inhibitor veli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In the current study we evaluated only static 18 F-DOPA PET parameters; as highlighted in a recent research on adult gliomas 40 , dynamic 18 F-DOPA PET analysis in pediatric gliomas might provide additional information in future investigations. Furthermore, in this study we did not compare 18 F-DOPA PET with advanced MR imaging modalities; as highlighted in a recent study which demonstrated a significant association of different advanced MR imaging metrics with survival 41 , prospective clinical trials should be performed in order to evaluate the synergic role of these techniques. We recognize that in the current study we did not evaluate the prognostic role of T/N, even though we used this parameter to stratify tumor uptake patterns and to delineate tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we evaluated only static 18 F-DOPA PET parameters; as highlighted in a recent research on adult gliomas 40 , dynamic 18 F-DOPA PET analysis in pediatric gliomas might provide additional information in future investigations. Furthermore, in this study we did not compare 18 F-DOPA PET with advanced MR imaging modalities; as highlighted in a recent study which demonstrated a significant association of different advanced MR imaging metrics with survival 41 , prospective clinical trials should be performed in order to evaluate the synergic role of these techniques. We recognize that in the current study we did not evaluate the prognostic role of T/N, even though we used this parameter to stratify tumor uptake patterns and to delineate tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are correlated with a worse prognosis while response to chemoradiotherapy has been associated with a decrease in tumor perfusion and BBB permeability. Increased DSC-CBV was found to be predictive of decreased progression free survival [ 20 , 116 , 117 , 118 , 119 , 125 , 126 , 127 ] and decreased OS [ 20 , 71 , 117 , 119 , 122 , 123 , 124 , 125 , 128 , 129 , 130 , 130 , 131 , 132 , 133 , 134 ] in diffuse cerebral gliomas. These parameters can be also used to follow-up on lower grade glioma lesions and to monitor treatment effects [ 122 , 135 , 136 ].…”
Section: Clinical Applications Of Hemodynamic Imaging In Gliomas—partmentioning
confidence: 99%
“…DSC-CBF has also shown a trend of significance for predicting time to recurrence but has been less commonly investigated. With respect of the DCE studies, increased Ktrans was shown to be associated with decreased PFS [ 140 , 141 , 142 , 143 ] and OS [ 125 , 143 , 144 , 145 , 146 ] in several studies. Of specific interest, the baseline elevated Ktrans in non-enhancing T2 lesions has been independently associated with negative PFS [ 141 ].…”
Section: Clinical Applications Of Hemodynamic Imaging In Gliomas—partmentioning
confidence: 99%
“…ADC histograms derived from the ADC of all voxels in a tumor volume are particularly well-suited to characterize the diffusion properties of the entire tumor volume in brain tumors and have been used to differentiate pediatric brain tumors by histologic type 29 and tumor grade. 30 ADC histogram parameters have also been associated with molecular subtype 31 and response to therapy 12,32 in diffuse intrinsic pontine gliomas in children. Herein, we report the use of ADC histogram metrics to identify prognosis and response criteria in refractory, recurrent, or progressive pLGGs treated with selumetinib.…”
Section: Discussionmentioning
confidence: 99%